Control of basal autophagy by calpain1 mediated cleavage of ATG5 - Xia, Hong-guang (2010)
Autophagy functions as an important catabolic mechanism by mediating the turnover of intracellular organelles and protein complexes. Although the induction of autophagy by starvation has been extensively studied, we still understand very little about how autophagy is regulated under normal nutritional conditions. Here we describe a study using a small molecule autophagy inducer, fluspirilene, as a tool to explore the mechanism of autophagy induction in normal living cells. We confirm the activity of fluspirilene in inhibiting Ca2+ flux. Furthermore, we show that reducing intracellular Ca2+ prevents the cleavage of ATG5, which in turn increases the levels of full length ATG5 and ATG12-ATG5 conjugate. Using siRNA mediated gene silencing, we demonstrate that inhibiting calpain1 is sufficient to induce autophagy in living cells. We conclude that calpain1 plays an important role in controlling the levels of autophagy in normal living cells by regulating the levels of a key signaling molecule, ATG12-ATG5 conjugate.